Política externa feminista: uma proposta teórico-metodológica a partir da categoria gênero - Chiuza, Sabrina da Costa (2024)
This research presents an analytical framework for studying Feminist Foreign Policy (FFP), integrating Joan Scott's (2007) four dimensions of gender - symbolic, normative, historical-cultural, and subjective - with Foreign Policy Analysis (FPA) and Feminist Methodology in International Relations (IR). To achieve this, a synthesis of scientific articles published on the topic between 2014 and June 2022 is intended, aiming to identify key elements within each gender dimension and to construct a theoretical-methodological proposal able to stimulate further research and assist policymakers in crafting gender-inclusive policies. In this way, this study is grounded on the understanding that feminist research is concerned with social justice, equality, and empowerment of marginalized groups, and one of the best ways to operationalize this is by paying attention to all gender dimensions. Furthermore, as it is recognized that international engagement is crucial for ensuring gender equality, it must also be reminded that such engagement should be guided by non-homogenizing policies that acknowledge gender experiences will vary according to geopolitical space. Hence, the concern for the subjective dimension of gender, enabling discussions on agency and the specificities of individuals involved in these processes. This research employs bibliometric analysis to map the study of Feminist or pro-gender Foreign Policy, followed by content analysis of the identified sample to synthesize findings and develop an analytical framework. Epistemologically, the research draws on dialectical materialism, understanding the reciprocal relationship between political practices and theoretical constructs.